Sociolinguistic styles - Hernández Campoy, Juan Manuel (Chichester, West Sussex, UK : Wiley-Blackwell, 2016)
"Sociolinguistic Styles systematically examines the complex phenomenon of style-shifting in sociolinguistics, focusing on its nature and social motivations, as well as on the mechanisms for its usage and its effects"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Rhetoric -- Social aspects; Discourse analysis -- Social aspects; Language and logic; Sociolinguistics; Electronic books